Pattern of land ownership and backwardness : a study of four villages in Jaunpur District of eastern U.P. - Shankar, Kripa 1927- (New Delhi : Ashish Pub. House, 1986)
Study based on July 1979-June 1980 data.
Includes bibliographical references and index.
Al Amin
Keywords: Land tenure -- India -- Jaunpur (District); Farm ownership -- India -- Jaunpur (District); Jaunpur (India : District) -- Economic conditions